Upaya Peningkatan Pengetahuan Ibu Melalui Edukasi ”Mengenal Infeksi Saluran Pernafasan Akut” - Annisa Nur Nazmi; Fransiska Erna Damayanti; Fajri Andi Rahmawan; Hirdes Harlan Yuanto; Ahmad Rosuli (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
ISPA is a group of diseases that causes the highest number of absenteeism when compared to other disease groups. The environment or residence is one of the factors that can influence the occurrence of ISPA. Environmental conditions that have poor levels of pollution and poor environmental sanitation can also be a cause of ISPA. Based on the results of interviews with PKK mothers in the Puri Brawijaya housing complex, the number of people affected by acute respiratory infections is quite high, especially toddlers, where this age is vulnerable to shortness of breath. Many factors trigger people to get ISPA. This community service aims to increase mothers' knowledge about the prevention and care of toddlers or children suffering from ISPA at home. The target of the activity was all PKK mothers in the Puri Brawijaya housing complex RT 04/RW 04, Kebalenan, Banyuwangi District, a total of 35 people. The method used was health education utilizing leaflets. The results of the activity showed that almost half of the participants had knowledge in the poor category, as many as 17 participants (46%). After the education, the majority of participants had knowledge in the good category, as many as 21 participants (57%). This activity showed an increase in mothers' knowledge about preventing and caring for toddlers/children with ARI by 11%.